Software for tolerance design - Shilo, Galina; Kovalenko, Daria; Gaponenko, Mykola (Видавництво Львівської політехніки, 2012)
Software for tolerance assignment and element selection is presented in the paper. Methods of tolerance design apply mathematical models of tolerance regions in shapes of hyperparallelepiped and hyperellipsoid which makes possible to take into consideration distribution laws of element parameters. The methods allow carrying element selection and tolerance assignment taking into account external influences. Specification of software functional characteristics and input data presentation were stated to provide integration with existing CAD-systems.
Keywords: tolerance design; radio-electronic devices; CAD systems; output functions; external influences; input data